Development Of Delphi-Based Learning Media in Electrical and Electronic Basic Students in SMKN 2 Serang - Irwanto Irwanto; Bagus Dwi Cahyono; Tubagus Umar Syarif Hadi Wibowo; Meilla Dwi Nurmala; Syamsul Rizal (Jurnal Pembelajaran Fisika, 2022)
The development of science and technology has a direct impact on the preparation of a qualified workforce, including the preparation of workforce graduates of Vocational High Schools. One of the learning materials in Vocational High Schools is basic material on electricity and electronics. Introduction to the basic material of electricity and electronics will be very difficult if only with books. Therefore, this study aims to create an interesting and interactive learning media. This media uses the Delphi program. In the learning media, there are materials and exercises for basic electricity and electronics subject matter for passive components of RLC. The design of this learning media development follows the ADDIE stage (Analyze, Design, Development, Implementation, Evaluation). The validation of this learning media program includes validating the content and design of the media itself. Based on the results of data analysis, it was found that the learning media developed in this study had a very high validity value from the two aspects assessed. For the validity of the learning media subject matter, the results of validation by experts are 3.61 and validation by the teacher is 3.6 so that it is very relevant to the concepts to be taught using this media, while for the validity of media design by experts is 3.5 and by the teacher 3.62 so that the learning media This research can be declared fit for use to support learning in school.Keywords: Learning media, Basic electricity and Electronics, development, delphiDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202203